Pengaruh Inflasi, Jumlah Uang Beredar, dan Nilai Tukar terhadap Indeks Saham LQ45 Periode Sebelum dan Selama Covid-19 (2018-2022) - Khrisdayanti, Arik; Manunggal, Syafrudin Arif Marah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The main issue in this study is how inflation, money supply, and exchange rates affect the LQ45 stock index before and during Covid-19 (2018-2022). The sample of this study includes 16 companies listed in the LQ45 index during February 2018 to July 2022. This research uses quantitative techniques and secondary data obtained from the websites of the Financial Services Authority, Bank Indonesia, and the Central Bureau of Statistics. The data analysis methods used include descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing which includes the t test, correlation coefficient, coefficient of determination, and f test. The findings of this study indicate that the money supply and exchange rate partially have a negative effect on the LQ45 stock index, while inflation has a positive and significant effect on the period during and before Covid-19 (2018-2022). Inflation, money supply, and exchange rates together have a significant effect on the LQ45 index share price before and during Covid-19. (2018-2022). Keywords: LQ45 Stock Index, Inflation, Money Supply, Exchange Rate.